SEEING MAXIM VIOLATION IN EFL INTERACTION - Soni, Mohammad; Dewi, Sinta; Alawiah, Sulistia (English Education and Applied Linguistics Journal (EEAL Journal), 2022)
In relating with other people, the cooperative principle may be done to make a dialogue run well and efficiently. However, there are chances when speakers have to violate a maxim because of some reason. Maxim of quality talks about; first, the participants in conversation. Second, they should not say something without adequate evidence. Maxim of quantity is concerned with providing information as required. It should not be less informative or more informative. Maxim of relevance recommends that the utterance should be relevant to the topic being conversed. Maxim of manner requires the speaker's utterance to be understandable or comprehensible or not ambiguous. It should be not be blurred. This study aims to determine the kinds of maxim violations done by the students during classroom interaction and the reasons behind the students violating the maxims. This study used observation and interview methods to collect the data. The study results show that there are three maxims violated by students, namely violating the maxim of quantity, relevance, and quality, with a total of 25 utterances. The students violate the maxim because they want to save face and build someone’s belief. This study found that the students violated three maxims when interacting with the teacher. They were violating the maxim of quality, violating the maxim of quantity, and violating the maxim of relevance. This study found 2 violating the maxim of quality, 14 violating the maxim of quantity, and 9 violating the maxim of relevance.